2007
DOI: 10.1161/atvbaha.107.149039
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Activation During Coronary Artery Surgery and Its Dose-Dependent Modulation by Statin/ACE-Inhibitor Combination

Abstract: Background-On-pump coronary artery bypass graft (CABG) surgery triggers an inflammatory response (IR) which may impair revascularization. The study aimed at (1) characterizing the temporal profile of the IR by assaying appropriate markers in both systemic and coronary blood, and (2) determining whether (and which doses of) cardiovascular drugs known to have antiinflammatory properties, namely statins and ACE-inhibitors (ACEI), inhibit the response. Methods and Results-Patients scheduled for CABG (nϭ22) were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…IL-6 is estimated to increase from about 1 pg ml À1 at BMI of 22 mg kg À2 to about 2.5 pg ml À1 at BMI of 37 mg kg À2 (a state of severe obesity) (Figure 4b). This increase was very limited in amount compared with the IL-6 level of post-cardiac disease, 91 post-coronary artery bypass surgery patients 92 or experimental low-dose entotoxemia in healthy human subjects. 81 It is not convincing that the slight IL-6 elevation can contribute to the development of obesity-related metabolic diseases.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 86%
“…IL-6 is estimated to increase from about 1 pg ml À1 at BMI of 22 mg kg À2 to about 2.5 pg ml À1 at BMI of 37 mg kg À2 (a state of severe obesity) (Figure 4b). This increase was very limited in amount compared with the IL-6 level of post-cardiac disease, 91 post-coronary artery bypass surgery patients 92 or experimental low-dose entotoxemia in healthy human subjects. 81 It is not convincing that the slight IL-6 elevation can contribute to the development of obesity-related metabolic diseases.…”
Section: Lack Of Bmi-adiponectin Association S-m Kuo and MM Halpernmentioning
confidence: 86%
“…It has also been reported that the safe and effective use of statins before and after CABG operations may acting as antiinflammatories that are independent of cholesterol levels [21]. Useful effects can also be obtained by suppressing the inflammatory response by administering higher than standard doses of statins before CABG [22]. In this study, when the results of Group R were evaluated it was concluded that levels of hs-CRP and IL-6,an inflammatory cytokines, could be reduced compared with Group C, and the levels of IL-10, an antiinflammatory cytokine, could be increased at certain times following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In RCTs, OPCAB has been associated with significantly lower myocardial injury and increase in inflammatory mediators compared with ONCAB,14, 15 although early mortality rates did not differ significantly 27. Nevertheless, it must be noted that the results of pharmacological treatment aimed at reducing the postoperative inflammatory reaction after CABG (corticosteroids, statins) have been mixed,28, 29 so the role of attempts to modulate inflammation in determining postoperative clinical outcome after CABG remains to be determined.…”
Section: Differences In Systemic Inflammatory Reaction and Platelet/cmentioning
confidence: 99%